MITD1 Deficiency Suppresses Clear Cell Renal Cell Carcinoma Growth and Migration by Inducing Ferroptosis through the TAZ/SLC7A11 Pathway. (22nd August 2022) - Zhang, Ye; Li, Yanze; Qiu, Qiangmin; Chen, Zhiyuan; Du, Yang; Liu, Xiuheng
Abstract : Clear cell renal cell carcinoma (ccRCC), the major histopathological subtype of renal cancer, is sensitive to ferroptosis. MIT-domain containing protein 1 (MITD1) has been reported to play an important role in hepatocellular carcinoma, while it remains unclear whether MITD1 is involved in ccRCC. Based on available data in The Cancer Genome Atlas, we found the expression of MITD1 increased through bioinformatics analysis and high MITD1 expression suggests a poor prognosis. And we validated that MITD1 expressed significantly in ccRCC through Western blot analysis. Then, we further compared the proliferation and migration capacity of ccRCC before and after MITD1 knockdown and further explored the effect of MITD1 knockdown on ferroptosis. The results indicated that MITD1 knockdown inhibited ccRCC cell proliferation and migration and induced ferroptosis in ccRCC. Furthermore, we found and analyzed the key molecule TAZ which was involved in ferroptosis caused by MITD1 knockdown. Subsequent overexpression experiments demonstrated that MITD1 knockdown induced ferroptosis and suppressed tumor growth and migration through the TAZ/SLC7A11 pathway. In summary, our study revealed the role of MITD1 in the ferroptosis of ccRCC and provided a novel target for ccRCC treatment.